Characteristics of Thyroid Nodule Patients Undergoing Radiofrequency Ablation (RFA) at RSUD Dr. Soetomo Surabaya from January 2023 to December 2024 - Afifudin, Muhammad (Jurnal Health Sains, 2025)
The availability of platelets in the Blood Donor Unit (UDD) of the Indonesian Red Cross (PMI) is relatively high each year. National data show that the number of platelet bags collected in 2019 reached 767,680 bags, increasing to 957,397 bags in 2021. However, the surge in dengue fever cases coinciding with the COVID-19 pandemic has nearly doubled the demand for concentrated platelets (TP) in hospitals since 2021. One method to extend platelet shelf life is the addition of platelet additive solution (PAS), which has not yet been implemented in Indonesia. This study aims to determine whether TP obtained through the buffy coat leukofiltered pooling method and stored with PAS can improve platelet quality during storage. The research methodology includes platelet quality analysis using several parameters, including platelet count, pH stability, and aggregation testing through adenosine diphosphate (ADP) examination of TP products over the storage period from day 0 to day 7. The results indicate that the addition of PAS helps maintain platelet quality, stabilize pH levels, and preserve platelet function during storage. This is made possible by the presence of key PAS components such as glucose, sodium acetate, sodium chloride, phosphate, magnesium, and potassium, which contribute to platelet stability and viability. The implications of this study suggest that implementing PAS in TP storage could serve as an effective solution for enhancing platelet availability while maintaining quality over an extended period. Therefore, adopting PAS in Indonesia’s platelet storage system could be a significant innovation to support blood supply sustainability, particularly in medical emergencies such as dengue fever outbreaks and pandemics.